Are audit fees discounted in initial year audit engagements? - Barua, Abhijit; Lennox, Clive; Raghunandan, Aneesh (Journal of Accounting and Economics, 2020)
Many studies report that audit fees are discounted in the year of an auditor change and regulators have long been concerned that such fee discounting could impair audit quality. We find significant bias in the way studies have tested for fee discounting. The bias exists because interim procedures are usually performed by both the predecessor and successor auditors but only the successor's fee needs to be disclosed. Accordingly, the disclosed fee during the auditor change year usually relates to a partial year of auditing services. We find that the evidence for fee discounting disappears after correcting for this measurement bias.